2012
DOI: 10.3996/082011-jfwm-047
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian Spawning Habitat Suitability Model for American Shad in Southeastern United States Rivers

Abstract: Habitat suitability index models for American shad Alosa sapidissima were developed by Stier and Crance in 1985. These models, which were based on a combination of published information and expert opinion, are often used to make decisions about hydropower dam operations and fish passage. The purpose of this study was to develop updated habitat suitability index models for spawning American shad in the southeastern United States, building on the many field and laboratory studies completed since 1985. We surveye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…; Hightower et al. ). Microhabitat use and suitability can be drastically different; thus, pooled fall and winter moderate and low gradient microhabitat use data were compared with spatially analogous microhabitat availability data to yield type III univariate habitat suitability criteria (HSCs; Bovee ; Newcomb et al.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…; Hightower et al. ). Microhabitat use and suitability can be drastically different; thus, pooled fall and winter moderate and low gradient microhabitat use data were compared with spatially analogous microhabitat availability data to yield type III univariate habitat suitability criteria (HSCs; Bovee ; Newcomb et al.…”
Section: Methodsmentioning
confidence: 98%
“…A multinomial distribution is used in instances where a trial produces one of several possible outcomes, such as a fish's selection of cobble (rather than clay or silt, for example) substrates for winter concealment (Hightower et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…Also, small‐scale diel position adjustments (discussed later) or low resolution in triangulating fish position could have obscured substrate selection for spawning. Research on other river systems in which American Shad spawn has indicated that shad spawn over relatively coarse substrates, such as gravel, cobble or boulders (Stier and Crance, ; Bowman, ; Hightower and Sparks, ; Hightower et al ., ). These substrates are typical of geomorphologic transitions between upland and coastal plain habitats, but they are not found in the St. Johns.…”
Section: Discussionmentioning
confidence: 97%
“…We also found that shad selected for deeper habitats in our spawning reaches. American Shad spawning has been reported at a range of depths (Massmann, ; Stier and Crance, ; Bowman, ; Hightower and Sparks, ; Hightower et al ., ). The wide range of substrate and depths used for spawning throughout the species' range suggests that depth and substrate selection could be secondary to locating suitable current velocity.…”
Section: Discussionmentioning
confidence: 99%
“…Passage was most likely at intermediate water temperatures (mean = 15.9°C) for American Shad, probably due to spawning motivation, as 15°C to 20°C is most suitable for spawning (Hightower et al. ); individuals were absent at LD‐1 at temperatures above 22.5°C. The probability of passage increased with water temperature (and arrival timing) for Flathead Catfish, again likely due to spawning motivation, as spawning movements have been observed between 17°C and 24°C (Daugherty and Sutton ).…”
Section: Discussionmentioning
confidence: 99%